Oncogenic potential of hepatitis B virus subgenotype D1 surpasses D3: significance in the development of hepatocellular carcinoma. (8th December 2017) - Datta, Somenath; Dasgupta, Debanjali; Ghosh, Alip; Ghosh, Suchandrima; Manna, Alak; Datta, Simanti; Chatterjee, Mitali; Chowdhury, Abhijit; Banerjee, Soma
Abstract : Contribution of HBV subgenotypes on the progression of liver diseases has been studied rarely. Here, the impact of two predominant HBV subgenotypes, D1 and D3 on the risk of development of HCC was investigated and found that HBV/D1 has more oncogenic potential than HBV/D3. Abstract: Despite widespread distribution of hepatitis B virus (HBV)-genotype D, the clinical implications of its ten subgenotypes (D1–D10) have not been well documented. Here, we have investigated the impact of two major circulating HBV/D subgenotypes, D1 and D3 in Eastern India towards pathogenesis of liver disease progression to hepatocellular carcinoma (HCC). HBV subgenotypes were determined using full-length genome sequences of HBV isolates from patients with chronic hepatitis B (CHB), liver cirrhosis (LC) and HCC. Impact of D1 and D3 on viral lifecycle and disease progression was assessed by several in vitro assays. Phylogenetic tree analysis revealed that HBV/D1 and HBV/D3 were the two predominating HBV subgenotypes circulating in Eastern India. Interestingly, the frequency of patients infected with HBV/D1 was noticed progressively rising from CHB to HCC through LC while the increasing frequency of HBV/D3 declined suddenly in HCC implicating HBV/D1 might have greater oncogenic potential than HBV/D3. Similar to higher viral load noted in HCC patients infected with HBV/D1 than HBV/D3, the larger amount of intracellular/extracellular viral DNA and secreted HBsAg levels in transfected cell lines also implicated that HBV/D1 might replicate faster than HBV/D3. Again, higher expression of marker genes related to endoplasmic reticulum stress, epithelial-mesenchymal transition, DNA double strand breaks, angiogenesis etc. and faster rate of cellular migration and anchorage independent growth cumulatively suggested that compared to HBV/D3, HBV/D1 generates more liver injuries which eventually culminates into HCC. Therefore, our results highlight the importance of determination of subgenotypes of HBV in CHB patients, so that high-risk individual can be monitor periodically that may help to detect HCC at early stages.